Pengembangan e-Modul dengan pendekatan STEAM untuk meningkatkan kemampuan berpikir kreatif matematis siswa - Priyatno, Sigit; Walid, Walid; Cahyono, Nur Adi (Universitas Muria Kudus, 2023)
This research aims to develop learning media for material on the rules of sines and cosines that is valid, effective and gets a positive response from students. The research method used is Research and Development (RD) with a 4-D model with stages 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The learning media developed resulted in a product called